THE PRO-INFLAMMATORY ROLE OF MICRORNA-29b IN DIABETIC NEPHROPATHY - NAWAL KHINTEEL JABBAR; ANWARA JASIB THAABAN ALMZAIEL; FERDOUS ABASS JABER (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objective of the study was to investigate the expression pattern of microRNA-29b (miRNA-29b) in patients with diabetic nephropathy (DN) compared to Type 2 diabetes mellitus (T2DM) and healthy subjects. Methods: Blood samples were obtained from 30 patients with DN, 30 patients with T2DM and 30 healthy subjects as controls. Serum reactive oxygen species (ROS) and interleukine-10 (IL-10) level were measured by enzyme-linked immunosorbent assay, and quantitative polymerase chain reaction was employed to screen the expression of serum miRNA-29b and anti-apoptotic B-cell lymphoma 2 (Bcl-2). Results: The results showed a significant increase in ROS levels (p<0.05) in DN group compared with T2DM and control groups. IL-10 levels were significantly increased compared to other groups (p<0.05). The gene expression of miRNA-29b was significantly increased with downregulation of Bcl-2 (p<0.05) in DN compared to T2DM and control groups (p<0.05). Conclusions: The study suggested that miRNA-29b expression is involved in the pathogenesis of DN. Hyperglycemia induced oxidative stress-mediated apoptosis, and an increase in expression of pro-inflammatory miRNA-29b exerts anti-protective effect by upregulating target genes related to inflammation and apoptosis, taken together, the results identify the regulatory role of miRNA-29b in DN.